The von Willebrand Factor Antigen Reflects the Juvenile Dermatomyositis Disease Activity Score - Ellie Gibbs; Amer Khojah; Gabrielle Morgan; Louis Ehwerhemuepha; Lauren M. Pachman (Biomedicines, 2023)
Objective: This study determined if an accessible, serologic indicator of vascular disease activity, the von Willebrand factor antigen (vWF:Ag), was useful to assess disease activity in children with juvenile dermatomyositis (JDM), a rare disease, but the most common of the pediatric inflammatory myopathies. Methods: A total of 305 children, median age 10 years, 72.5% female, 76.5% white, with definite/probable JDM at diagnosis, were enrolled in the Ann & Robert H. Lurie Cure JM Juvenile Myositis Repository, a longitudinal database. Disease Activity Score (DAS) and vWF:Ag data were obtained at each visit. These data were analyzed using generalized estimating equation (GEE) models (both linear and logistic) to determine if vWF:Ag reflects disease severity in children with JDM. A secondary analysis was performed for untreated active JDM to exclude the effect of medications on vWF:Ag. Result: The vWF:Ag test was elevated in 25% of untreated JDM. We found that patients with elevated vWF:Ag had a 2.55-fold higher DAS total (CI95: 1.83–3.27, p < 0.001). Patients with difficulty swallowing had 2.57 higher odds of elevated vWF:Ag (CI95: 1.5–4.38, p < 0.001); those with more generalized skin involvement had 2.58-fold higher odds of elevated vWF:Ag (CI95: 1.27–5.23, p = 0.006); and those with eyelid peripheral blood vessel dilation had 1.32-fold higher odds of elevated vWF:Ag (CI95: 1.01–1.72, p = 0.036). Untreated JDM with elevated vWF:Ag had more muscle weakness and higher muscle enzymes, neopterin and erythrocyte sedimentation rate compared to JDM patients with a normal vWF:Ag. Conclusion: vWF:Ag elevation is a widely accessible concomitant of active disease in 25% of JDM.